Darwin and Newton- Lives (Not) parallel - Athanasiou, Kyriacos (Researchgate, DOI: 10.13140/RG.2.2.24607.53928, 2023)
Darwin and Newton: Lives (Non) Parallels. On the 20th of March, we are to honor the death of Isaac Newton as we celebrated previously, Darwin's Day in middle February. Much has been written about their work, but I just want to remind that in 1859 Darwin published his findings in the book "The Origin of Species", arguing that the species of living organisms do not remain unchanged, as Aristotle and the book of Genesis argued, but have a common origin and through natural selection evolve over millennia. This position generated strong reactions from the first moment, mainly from the Church, who believes that the creation of the world is the result of Divine Grace. Darwin was labeled an atheist and mocked as a descendant of monkeys, while some of his supporters were dragged to court (Trial of the Apes). Today, more than a century after his death, the scientific community has accepted his theory, which has since been verified through numerous observations and newer discoveries. A recent visit to the Mausoleum at Westminster in London made me think and led me to write this text